The motivation factors to participate in Physical Activity (PA) among persons with hearing impaired - Nagoor Meera Abdullah; Nasthasia Wateh; Mohamad Nizam Mohamed Shapie; Mohamad Rahizam Abdul Rahim; Mohd Sofian Omar-Fauzee; Mohamad Nizam Nazarudin (Academic Inspired Network, 2019)
The involvement among person with disabilities (PWD) in physical activity related to the health and social benefits. The benefits are such as to develop some new skills, the opportunity to meet new friends and also to increase the confidence level among them. Thus, the purpose of this study is to determine the motivation factors to participate in physical activity among persons with hearing impaired ability. A total of 100 (n=100) persons with hearing impaired (male N=50, female N=50) aged range from 13 to 25 participated in the study. Motivation for physical activity was assessed by 40-items of Physical Leisure and Motivation Scale (PALMS) which measured eight motives developed by Molanourouzi, Khoo and Morris (2014). Statistical Package for the Social Sciences (SPSS) version 21 was used to analyze the descriptive and inferential data. The Independent T-test was used to measure the motivation level and difference motivation factor between the male and the female participants. The Cronbach alpha was used to check the Internal Consistency of the PALMS. Results revealed the female and the male participants had different motivation factors to participate in physical activity. Five highest motivations among the male are enjoyment (4.62±0.714), mastery (4.60±0.495), psychological condition (4.40±0.495), affiliation (4.30±0.544) and physical condition (4.20±0.606). The female tends to competition / ego (4.78±4.122), physical condition (4.52±0.614), enjoyment (4.48±0.609), mastery (4.48±0.646) and affiliation (4.36±0.631). There was no significant different on motivation between the genders among the person with hearing impaired (t (98) =-1.14, p>.05). It can be concluded that a person with disability can reduce his or her negative perception when participating in physical activity.